Analysis of the Implementation of Value Added Tax (VAT) with Changes in the Optimization of Tax Base (TB) in Distribution and Trading Companies in Surabaya - Anam, Sahrul; Vendy, Vicky (Universitas Muhammadiyah Tangerang, 2025)
This research examines the implications of Value Added Tax (VAT) applied by the Calculation and Trade Distribution Company in Surabaya on the change in the PMK Number 131 rule related to the calculation of the optimized tax base to 11/12. The research method used is qualitative description. The data used is primary data with data collection techniques from observation, documentation, and interviews with parts of the accounting unit and outside accounting that are directly related to Value Added Tax (VAT). The results of the research at the Distribution and Trading Company in Surabaya explained that the calculation of the 11/12 Tax Base does not have its value for the company, the problem faced comes from the new Coretax system when inputting data to reporting Value Added Tax (VAT). This study found that the application of Tax Base optimization in Distribution and Trading Companies in Surabaya does not affect the price of goods in purchasing and sales activities, meaning that the price of goods remains the same as the application of the 11% rate , this finding shows that the optimization that occurs only changes the way the Tax Base is calculated, not the increase in the price of goods.This research provides an important dedication in optimizing the implementation of the Tax Base for VAT in companies located in Indonesia, as well as providing an understanding to the public regarding the 11% and 12% taxation phenomena that have been in effect since early 2025. Keyword: Value Added Tax (VAT) Rates, Calculation of Tax Base (TB), Distribution and Trading Companies, Coretax, Tax Regulations.